Forensic investigation of falsified antimalarials using isotope ratio mass spectrometry: a pilot investigation - Newton, PN; Chesson, LA; Mayxay, M; Dondorp, A; Tabernero, P; Howa, JD; Cerling, TE (Springer Nature, 2024)
We explored whether isotope ratio mass spectrometry (IRMS) is useful to investigate the origin of falsified antimalarials. Forty-four falsified and genuine antimalarial samples (artesunate, artemether-lumefantrine, dihydroartemisinin-piperaquine and sulphamethopyrazine-pyrimethamine) were analyzed in bulk for carbon (C), nitrogen (N), and oxygen (O) element concentrations and stable isotope ratios. The insoluble fraction (“starch”) was extracted from 26 samples and analyzed. Samples of known geographical origin maize, a common source of excipient starch, were used to produce a comparison dataset to predict starch source. In both an initial (n = 18) and a follow-on set of samples that contained/claimed to contain artesunate/artemether (n = 26), falsified antimalarials had a range of C concentrations less than genuine comparator antimalarials and δ13C values higher than genuine comparators. The δ13C values of falsified antimalarials suggested that C4 plant-based organic material (e.g., starch derived from maize) had been included. Using the known-origin maize samples, predictions for growth water δ18O values for the extracted “starch” ranged from − 6.10 to − 1.62‰. These findings suggest that IRMS may be a useful tool for profiling falsified antimalarials. We found that C4 ingredients were exclusively used in falsified antimalarials versus genuine antimalarials, and that it may be possible to predict potential growth water δ18O values for the starch present in falsified antimalarials.